FORMULASI DAN EVALUASI FISIK SEDIAAN SERUM ANTI-AGING YANG MENGANDUNG EKSTRAK TANAMAN DARI BERBAGAI LITERATUR - Bheta Sari Dewi; Ayu Werawati (KOLONI, 2022)
Currently, beauty products are developing very fast, especially anti-aging facial care products. One of the most popular products is serum. Serum contains many concentrates that are useful for nourishing and moisturizing the skin. Several plants that have been studied have the potential to be used as serum preparations, namely apuh-apuhan leaves, brown rice, Malacca fruit, gotu kola, jamblang leaves, cempedak leaves, black pepper, and Perilla Frutescens. This study aims to determine the formulation and physical evaluation of serum preparations containing plant extracts in terms of various literatures. The method used is descriptive literature review by collecting various sources from several national journals. The number of national journals used is 7 and 1 international journal. The results of a literature study on serum formulations containing plant extracts can be formulated into serum dosage forms. Evaluation of serum preparations includes organoleptic tests, pH tests, spreadability tests, and viscosity tests. The results of the study concluded that the formulation with the most complete physical evaluation and had good stability without any signs of damage to the dosage form in the serum formulation with a pH value of 5.5, a spreadability of 6.63 cm and a viscosity value of 2900 cP were found in formulations containing the extract. malacca fruit plants. Keywords: anti-aging, serum, formulation, evaluation, extract